Pengaruh Kecepatan Putaran Mesin Terhadap Hasil Coco Fiber dan Coco Peat Buah Kelapa dari Daerah Jambi - Sepriyanto; Emmistasega Subama (LPPM Politeknik Jambi, 2018)
The influence of rotation engine speed to coco fiber and coco peat yieldof coconut fruit from Jambi area has been done. The study aims to know the percentage of cocofiber and cocopeat produced based on the influence of rotation engine speed of decomposition machine starting from 225 rpm, 450 rpm, 750 rpm and 900 rpm. Each round speed will operate for 2 minutes with 500 grams of raw material and use variation 5 and10 decomposing blades. The result show that(1) the rotational speed of the decomposition machine affects the amount of cocofiber and cocopeat produced. The highest percentage of cocofiber and cocopeat is at 450 rpm (2) The number of blades of the decomposition machine against the percentage of cocofiber and cocopeat produced. The highest percentage of cocofiber and cocopeat using 10 blades. (3) The maximum result of cocofiber and cocopeat obtained from engine speed 450 rpm is 28% cocofiber and 50% cocopeat.